PENGARUH KARAKTERISTIK PERUSAHAAN DAN BEBAN IKLAN PADA TINDAKAN PENGHINDARAN PAJAK - Sugitha, I Made Yogi Pradnyana; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
This study aims to demonstrate empirically the effect of company characteristics and advertising expenses at tax avoidance measures. Characteristics measured by the company's liquidity, leverage, profitability, company size, and earnings quality. The population in this study were 126 companies listed in Indonesia Stock Exchange 2010-2014. The sampling technique used was purposive sampling, so he found the number of observations of 130 observations that meet the criteria of the sample. The data analysis technique used to test the hypothesis in this study is multiple linear regression analysis. The results showed that the variable size of the company has a negative influence on ETR. Variable liquidity, earnings quality, and advertising expenses had a positive influence on ETR, while variable leverage and profitability no effect on ETR.
Keywords: Likuiditas, Leverage, Profitabilitas, Ukuran Perusahaan, Kualitas Laba, Beban Iklan, Effective Tax Rate